Remodeling of Kalri Baghar (K.B) Feeder - ATTA MUHAMMAD PHUL; BAKHSHAL KHAN LASHARI; KHALIFA QASIM LAGHARI (Mehran University Research Journal of Engineering and Technology, 2010)
The shortage of irrigation water supplies and reduced water carrying capacity of Kalri Baghar (K.B) feeder require remodeling of the canal (an off-taking canal from right bank of Indus River at Kotri Barrage). The designed normal supply level (NSL) capacity of K.B feeder was 257 cumecs (9100 cusecs), but it has now maximum flow rate of 241 cumecs (8500 cusecs) due to damaged cross-section and silted normal flow area. In present condition only culturable command area (C.C.A) needs 277 cumecs, and the requirement of water supply is additional. The hydraulic parameters are revised up to its potential and remodeled the canal using C++ simulation model based on Lacey?s Method and FlowMaster Model. Using these models present discharge is enhanced 5, 10, and 20%, which revealed changes in hydraulic parameters of the canal. The total length of the canal is 5761 m (18,900 ft) in which there is 4% of stone pitching and concrete lining and rest of the channel is passing through sandy loam soil, rocks and coarse sand areas. The regime (stable earthen) channel cross-section is remodeled using Lacey?s method. The stone and concrete lined section is redesigned by Manning?s procedure using FlowMaster simulation model. It is required and feasible to modify water carrying capacity of the NSL of the channel by 20% as compared to current conditions.